Value of Positron Emission Tomography/Computed Tomography (PET-CT) in Suspected Non-small Cell Lung Cancer Recurrence and Impact on Patient Management - Beslic, Nermina (Acta Inform Med, 2016)
INTRODUCTION: Positron emission tomography/computed tomography (PET-CT) is very sensitive for diagnosis of recurrent NSCLC and has a significant impact on change of management. Preliminary data suggest superiority of PET-CT comparing to CT alone for lung cancer restaging. MATERIALS AND METHODS: This is a retrospective study which aim is to validate usage of PET-CT in suspected non-small cell lung carcinoma recurrence and its impact on further patient management. Total number of 31 patients with non-small cell lung carcinoma and uncertain diagnosis of recurrent disease or its extent after routine clinical and CT work-up were enrolled in this study. DISCUSSION: We found in our study that PET-CT diagnosed recurrent disease in 65% of patients who were previously presented with an indeterminante CT. In 85% of patients there were change in further management. CONCLUSION: We suggest that PET should be performed on patients who have suspected relapse after potentially curative treatment, particularly if active treatment is being considered. PET-CT improved the diagnosis of recurrent NSCLC and this resulted in a significant impact and change in further patient management.